The effect of solvent accessible surface on Hammett-type dependencies of infinite dilution (29)Si and (13)C NMR shifts in ring substituted silylated phenols dissolved in chloroform and acetone - Blechta, Vratislav; Sabata, Stanislav; Sýkora, Jan; Hetflejš, Jiří; Soukupová, Ludmila; Schraml, Jan (Magnetic resonance in chemistry, 2012)
Infinite dilution (29)Si and (13)C NMR chemical shifts were determined from concentration dependencies of the shifts in dilute chloroform and acetone solutions of para substituted O-silylated phenols, 4-R-C6 H4 -O-SiR'2 R″ (R = Me, MeO, H, F, Cl, NMe2, NH2, and CF3), where the silyl part included groups of different sizes: dimethylsilyl (R' = Me, R″ = H), trimethylsilyl (R' = R″ = Me), tert-butyldimethylsilyl (R' = Me, R″ = CMe3), and tert-butyldiphenylsilyl (R' = C6 H5, R″ = CMe3). Dependencies of silicon and C-1 carbon chemical shifts on Hammett substituent constants are discussed. It is shown that the substituent sensitivity of these chemical shifts is reduced by association with chloroform, the reduction being proportional to the solvent accessible surface of the oxygen atom in the Si-O-C link.
Keywords: 1H NMR; solvent accessible surface; chemical shifts; substituent effects; 29Si NMR; Hammett-type dependence; 13C NMR